Colorectal Cancer Screening Disparities for Rural Minorities in the United States - Allison M. Cole; J. Elizabeth Jackson; Mark Doescher (SAGE Publishing, 2013)
Background: Despite the existence of effective screening, colorectal cancer remains the second leading cause of cancer death in the United States. Adults living in rural areas and members of minority populations both experience disparities in colorectal cancer screening. Methods: Cross-sectional prevalence study of Behavioral Risk Factor Surveillance System from the Centers for Disease Control from 1998 to 2005. Primary outcome : Predicted probability of reporting timely colorectal cancer screening. Independent variables : rural residence, race/ethnicity. We adjusted for demographic and socioeconomic characteristics of respondents. Results: After adjustment rural non-Hispanic whites (44.3%), rural African American/blacks (44.8%), urban and rural Hispanic/Latinos (43.7% and 40.8%, respectively), urban and rural American Indian/Alaska Natives (45.8% and 46.8%), and urban and rural Asians (35.4% and 39.6%) had lower compared with urban non-Hispanic whites (49.5%; P < .05% for all comparisons). Urban Asians were least likely to report use of fecal occult blood testing (8.6%, 95% confidence interval = 6.3% to 10.9%) and rural Asians were least likely to report use of endoscopy screening (21.2%, 95% confidence interval = 16.2% to 26.2%). Discussion: Rural minorities may face different barriers to colorectal cancer screening than urban minorities or rural non-Hispanic whites. Further research to develop interventions to improve screening in these populations is warranted.